2019
DOI: 10.1101/792184
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cathepsin g degrades synovial fluid lubricin: relevance for osteoarthritis pathogenesis

Abstract: Lubricin (PRG4) is a mucin type protein that plays an important role in maintaining normal joint function by providing lubrication and chondroprotection. Improper lubricin modification and degradation has been observed in idiopathic osteoarthritis (OA), while the detailed mechanism still remains unknown. We hypothesized that the protease cathepsin G (CG) may participate in degrading lubricin in synovial fluid (SF). The presence of endogenous CG in SF was confirmed in 16 patients with knee OA. Recombinant human… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…Despite this lower level of CTSG in RA patients, Gao et al (15) found that the synovial fluid of RA patients has a higher level of CTSG than that of healthy controls, which leads this study to suspect a higher level of CTSG in those patients compared to healthy controls. It is also believed that this increase in CTSG level may be due to the release of a protease enzyme by neutrophils during inflammation (18) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite this lower level of CTSG in RA patients, Gao et al (15) found that the synovial fluid of RA patients has a higher level of CTSG than that of healthy controls, which leads this study to suspect a higher level of CTSG in those patients compared to healthy controls. It is also believed that this increase in CTSG level may be due to the release of a protease enzyme by neutrophils during inflammation (18) .…”
Section: Discussionmentioning
confidence: 99%
“…Rheumatoid arthritis patients with disease duration less than six months have slightly higher CTSG levels, may due to increased inflammatory immune response in the early stages of RA that stimulates the recruitment and activation of neutrophils in the joints (21) . As part of the immunological response, neutrophils produce and release CTSG (18) . The low levels of CTSG in RA patients with disease duration more than six months may be related to long-term use of medications for RA, which can reduce inflammation and slow disease progression.…”
Section: Discussionmentioning
confidence: 99%